Effect of estradiol on cognition in men undergoing androgen deprivation therapy: A randomized placebo‐controlled trial. (21st February 2022) - Russell, Nicholas; Allebone, James; Dandash, Orwa; Hoermann, Rudolf; Cheung, Ada S.; Zajac, Jeffrey D.; Handelsman, David J.; Kanaan, Richard A.; Grossmann, Mathis
Abstract: Objective: Roles for estradiol in modulating cognition in men remain uncertain. We assessed the isolated effects of estradiol on cognition in men in the absence of testosterone. Design: Randomized trial of transdermal estradiol 0.9 mg daily, or matched placebo, for 6 months, hypothesizing that estradiol would improve verbal learning, verbal memory, and spatial problem solving over time. Patients: Men receiving androgen deprivation therapy (ADT) for prostate cancer. Measurements: Cognition was assessed by a tablet‐based cognitive battery (Cogstate) at baseline, Month 1, Month 3, and Month 6. Anxiety and depression symptoms were assessed using the Hospital Anxiety and Depression Scale. Results: Seventy‐eight participants were randomized. Baseline mean scores were 21.0 (standard deviation [ SD ] 4.1) for the International Shopping List test (ISL), assessing verbal learning and memory (higher scores better), and 60.4 ( SD 19.5) for the Groton Maze Learning test (GML), assessing spatial problem solving (lower scores better). There was no significant difference in performance over time for the estradiol group versus the placebo group for the ISL, mean adjusted difference (MAD) 0.7 (95% confidence interval [CI] −1.2 to 2.5), p = .36, or the GML, MAD −3.2 (95% CI −12.0 to 5.6), p = 0.53. There was no significant difference between groups over time in performance in any other cognitive domain, or on depression or anxiety scores. Conclusions: We found no major effects of estradiol on cognition in men with castrate testosterone concentrations. Although the cognitive effects of ADT are debated, this study suggests that any such effects are unlikely to be prevented by the administration of estradiol.